Is Penguin Circovirus Circulating Only in the Antarctic Circle? Lack of Viral Detection in Namibia - Laura C. Roberts; Umberto Molini; Lauren M. Coetzee; Siegfried Khaiseb; Jean-Paul Roux; Jessica Kemper; David G. Roberts; Katrin Ludynia; Marcus Doherr; Darrell Abernethy; Giovanni Franzo (Animals, 2023)
The known host range of circoviruses is continuously expanding because of more intensive diagnostic activities and advanced sequencing tools. Recently, a new circovirus (penguin circovirus (PenCV)) was identified in the guano and cloacal samples collected from Adélie penguins (Pygoscelis adeliae) and chinstrap penguins (Pygoscelis antarcticus) in Antarctica. Although the virus was detected in several asymptomatic subjects, a potential association with feather disease was speculated. To investigate the occurrence and implications of PenCV in other penguin species located outside of Antarctica, a broad survey was undertaken in African penguins (Spheniscus demersus) on two islands off the southern Namibian coast. For this purpose, specific molecular biology assays were developed and validated. None of the 151 blood samples tested positive for PenCV. Several reasons could explain the lack of PenCV positive samples. African penguins and Pygoscelis species are separated by approximately 6000 km, so there is almost no opportunity for transmission. Similarly, host susceptibility to PenCV might be penguin genus-specific. Overall, the present study found no evidence of PenCV in African penguin colonies in Namibia. Further dedicated studies are required to assess the relevance of PenCV among different penguin species.